ANALISIS BIOAUTOGRAFI DAN UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP BAKTERI Propionibacterium acne - Nasution, Haris Munandar; Situmorang, Rati Satri (Jurnal Farmanesia, 2022)
Noni or (Morinda citrifolia L.) contains active anthraquinone, scaloptin, flavonoid, and adaptogen compounds that have antifungal and antimicrobial effects. Antibacterial chemicals have many negative side effects, and other alternatives are needed as antibacterials, one of which is by using noni. This study aims to analyze bioautography and determine the antibacterial activity of noni leaf ethanol extract against Propionibacterium acne bacteria.